Strategi Supervisi Akademik Pembelajaran Mendalam Di SMAN 2 Tualang Kabupaten Siak - Lestari, Dian; Bustari, Meilina (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the strategy of academic supervision in supporting the implementation of deep learning within the Merdeka Curriculum at SMAN 2 Tualang, Siak Regency. The research employed a qualitative approach using a case study design. Data were collected through interviews, observations, and documentation involving the principal, vice principal for curriculum affairs, and teachers. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation and technique triangulation. The findings revealed that academic supervision was implemented through individual supervision techniques, particularly classroom observations, which were carried out systematically through planning, implementation, and follow-up stages. The planning stage included the preparation of supervision programs, schedules, instruments, and learning documents. The implementation stage focused on observing classroom learning activities and the application of deep learning principles. Follow-up activities were conducted through reflective discussions, feedback, mentoring, workshops, and teacher learning communities. Supporting factors included teacher commitment, principal support, a conducive school culture, effective communication, and adequate learning facilities. Meanwhile, inhibiting factors included differences in teacher competence, limited time, administrative workload, and budget constraints for professional development programs. The study concludes that academic supervision plays a significant role in strengthening deep learning implementation and enhancing teachers’ professional competence in the Merdeka Curriculum.